The Analysis of National Road User Satisfaction in Urban Area (Case Study of The PGC-Kramat Jati-Graha Cijantung Route, Jakarta) - Jody Andrian Muatan; Andri Irfan Rifai; Susanty Handayani (Indonesian Journal of Multidisciplinary Science, 2022)
Jalan Raya Bogor is a national road that connects the cities of Jakarta, Bogor, and Depok. Therefore, this national road is significant for the surrounding community to carry out activities and even affect the surrounding economy. Therefore, the quality of road services such as road pavement conditions, road shoulder conditions, drainage/waterway conditions, complementary road conditions, markings, signs, condition of complementary road buildings, and condition of plants/grass around the road are essential indicators for achieving good road service. Therefore, identification is needed regarding the evaluation of road service performance by applying the following aspects of the provisions of the road terms applicable in Indonesia. Furthermore, the most important thing is the achievement of community needs in transportation activities. Therefore, this study aims to identify the performance of road services in terms of the level of importance and the level of application of road infrastructure components in the perception of road users with the methods used using the Customer Satisfaction Index and Importance Performance Analysis analysis.